A Survey on the Chinese Language Placement Test in China - Lian, Luo (Sinología hispánica. China Studies Review, 2017)
Placement test is the starting point of any language teaching programs, and it is the foundation of learner-centered teaching. However, very few researches on placement tests have been done in this field, and the general situation of these tests in China are rarely known to the researchers. Therefore, this paper investigates the problems in the placement test of teaching Chinese as foreign language by the approach of questionnaire, intending to draw attention from various language teaching institution and attract more researchers to conduct in-depth further researches in this field.